(untitled) (Journal of Human Sciences, 2022)
The phenomenon of immigration or asylum is widespread among Muslims in general and young people in particular in most Arab and Islamic countries. Migration has become a dream and aspiration for some young people. This is not surprising, because it is a requirement of God’s universal laws for man to move and migrate from one place to another. That some do not know that this is a dangerous indicator for their lives, and from the above, the research problem revolves around the basic question: What is the legal perspective for the immigration of countries whose systems are under the authority of the infidels? The research aims to clarify migration and its provisions, and to show its divisions. The study uses the inductive approach to reach this end. The researcher reached the most important results represented in: The migration of Muslims to the lands of infidels has several jurisprudential rulings that differ according to the person’s condition and the circumstances in which he lives, namely: the Muslim practices the rituals of Islam there, and it is forbidden for the Muslim if he is unable to show his religion in the lands of the infidels, and migration is permissible according to Sharia. If necessary, as if to protect himself from the tyranny of the ruler.